Detailed Analysis of Focal Chromosome Arm 1q and 6p Amplifications in Urothelial Carcinoma Reveals Complex Genomic Events on 1q, and SOX4 as a Possible Auxiliary Target on 6p. - Pontus Eriksson (Public Library of Science (PLoS), 2013)
Background Urothelial carcinoma shows frequent amplifications at 6p22 and 1q21-24. The main target gene at 6p22 is believed to be E2F3, frequently co-amplified with CDKAL1 and SOX4. There are however reports on 6p22 amplifications that do not include E2F3. Previous analyses have identified frequent aberrations occurring at 1q21-24. However, due to complex rearrangements it has been difficult to identify specific 1q21-24 target regions and genes. Methods We selected 29 cases with 6p and 37 cases with 1q focal genomic amplifications from 261 cases of urothelial carcinoma analyzed by array-CGH for high resolution zoom-in oligonucleotide array analyses. Genomic analyses were combined with gene expression data and genomic sequence analyses to characterize and fine map 6p22 and 1q21-24 amplifications. Results We show that the most frequently amplified gene at 6p22 is SOX4 and that SOX4 can be amplified and overexpressed without the E2F3 or CDKAL1 genes being included in the amplicon. Hence, our data point to SOX4 as an auxiliary amplification target at 6p22. We further show that at least three amplified regions are observed at 1q21-24. Copy number data, combined with gene expression data, highlighted BCL9 and CHD1L as possible targets in the most proximal region and MCL1, SETDB1, and HIF1B as putative targets in the middle region, whereas no obvious targets could be determined in the most distal amplicon. We highlight enrichment of G4 quadruplex sequence motifs and a high number of intraregional sequence duplications, both known to contribute to genomic instability, as prominent features of the 1q21-24 region. Conclusions Our detailed analyses of the 6p22 amplicon suggest SOX4 as an auxiliary target gene for amplification. We further demonstrate three separate target regions for amplification at 1q21-24 and identified BCL9, CHD1L, and MCL1, SETDB1, and HIF1B as putative target genes within these regions.